Evaluation of the Sustainability of Urban Agriculture in the Use of Yard Land in the City of Yogyakarta, Indonesia - Lantarsih, Retno; Suhartini, Suhartini; Gupta, Anu (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2024)
Utilizing yard is an alternative to increasing food security. The government is rolling out a program for using yard through the Pekarangan Pangan Lestari Program (P2L) to respond to the threat of a food crisis due to global climate change, increasing population, and land conversion. Most P2L Program recipients in Yogyakarta City do not work as farmers. Therefore, there is a need to study P2L Program evaluation candidates in Yogyakarta City. The aim of this research is to (1) evaluation a P2L Program in the City of Yogyakarta, which includes ecological, economic and social dimensions, and (2) determine sensitive attributes in the sustainability of the P2L Program. This research is exploratory, and samples were taken using the proportional random sampling method. The types of data used include primary and secondary data. This research uses multidimensional scale analysis (MDS) to assess the status and stability index of the P2L Program and to identify components that influence its stability index for each aspect by using leverage analysis. Multidimensional Scaling using Rapfish is a relevant approach that involves policies or programs. The research results show that the Yogyakarta City P2L Program has a desired index for the social dimension of 62.63%, which is quite sustainable. In the less sustainable category, the ecological and economic dimensions are 48.69% and 33.38%, respectively. For the sustainability of the P2L Program, the social dimension has the greatest impact. Sensitive attributes in the development of P2L in Yogyakarta City include the utilization of fertilizer from household waste, the beauty of yards, establishing cooperation with partners for product marketing, familiarity between members, establishing communication, absorbing labour, and saving expenses.